GRAPH DATABASE AND SQL DATABASE: A Comparative Study - Lukman Hadijanto (ENSAINS JOURNAL, 2019)
AbstractToday's reality is that everything being more and more interconnected. And as reality being developing into that situation, the information realm has to cope with this new situation - more interconnected, more interrelated objects. One important component in managing information is database. The current established database is relational database, in which information of objects are saved in tables, and their relationship with other objects in foreign key constraints. This relational database is proven to be reliable and robust, but there is a new database development where the interconnectivity between objects being the focus. This new kind of database is called graph database.As a new breed of database, we want to compare graph database with the established relational database. Having some works been done on this database comparison,  here we focus on  the subjective and objective review of usage easiness and the response time of graph database compared to relational databaseAs the result, querying graph database is more natural than relational database. The cypher query language is easy to understand and intuitive. Adding depth of query in cypher language is just like adding a link of a chain. On the other hand, the query response time of relational database is much better than graph database. Current implementation of graph database is still less impressive than relational database in term of time performance. Relational database is still the promising choice for time-critical application.